Wacana Politik Dan Kepemimpinan Islam Dalam Naskah Kuno Kesultanan Bima - Mukhlis Mukhlis (Universitas Islam Negeri Mataram, 2005)
Islamic thought in the field of politics and leaderships is found as the Muslims effort ellaborating basic values of Islamic teachings considered relevant to and applicable in the two fields, mainly in the governmental arrangement and the conduct of ruling persons. The effort is based on the point of view that politics needs some values ordering it so that it as part of human existence (zoon politicon) is able to lead all human beings to a glorified life, not to split them into a lawless and orderless life (homo homini lupus). The effort has been lasting over centuries since the forming of established Muslims community in Madinah. One of sources from wich Muslim thought in the two field in certain period in the long journey of the history of Islam can be traced is manuscripts. Through historical and philological approaches, the outhor took a study on one of heritage manuscripts of Bima Sultanate that was produced in 1882, Jawharat al-Ma‘ârif. Applaying content analysis the outhor picture out the model of Islamic political and leadership tought in the manuscript. Seeing from the three theoretical perspectives concerning the two field, the outhor concluded that the manuscript in line with the third theory which stated that Islam—through al-Qur’an and Sunnah—only has a set of ideal and ethical values concerning the to filed. The ellaboration and practical implementation of the values always follow the local contexts of Muslim communities—in this manuscript the contexts Bimanese Muslim in the 19th century.